Genome macrorestriction analysis of diversity and variability of Pseudomonas aeruginosa strains infecting cystic fibrosis patients. - Struelens, M J (1993)
Genome macrorestriction fingerprinting with XbaI and DraI was used to analyze the relatedness of 166 Pseudomonas aeruginosa isolates collected from 31 cystic fibrosis patients over a 1- to 20-month period and to correlate their genotype with patterns of resistance to 14 antimicrobial agents. Quantitative comparison of intra- and interpatient similarities of P. aeruginosa macrorestriction patterns disclosed two discrete ranges that clearly discriminated subclonal variation (> 80% relatedness) and clonal diversity (10 to 70% relatedness). Cloning-derived mutants exhibited up to 20% divergence of genomic macrorestriction patterns during the course of chronic colonization of individual patients. Change of susceptibility to multiple antimicrobial agents developed in 50% of sequential pairs of isolates from individual patients. Only 19% of these susceptibility changes were attributable to strain substitution, while the majority (56%) of resistance changes were associated with minor genomic variations of a persistent strain. Sixty-six percent of patients harbored one strain, and 33% carried two strains. Three common strains colonized 5 (28%) of 18 patients attending a cystic fibrosis clinic, and another two strains colonized two patient pairs (31%) of 13 patients staying at a rehabilitation center, suggesting potential cross-infection in these settings. By indexing regional polymorphisms throughout the chromosome structure, macrorestriction analysis can monitor subclonal evolution of P. aeruginosa and identify isogenic resistance mutants. Quantitative macrorestriction fingerprinting enables discrimination between clonal variants and clones of distinct origins and should therefore provide a reliable tool for investigating the mode of acquisition of P. aeruginosa in cystic fibrosis patients.